An electron microscopic and biochemical study of the potential protective effect of ginger against Cadmium-induced testicular pathology in rats - Motawee, Moustafa E.; Damanhory, Ahmed A.; Sakr, Hany; Khalifa, Mohamed Mansour; Atia, Tarek; Elfiky, Mohamed M.; Maher, Muhammad; Sakr, Hader I. (Frontiers in Physiology, 2022)
Background: Cadmium (Cd) is a toxic heavy metal used in many industries. Since the second half of the 20th century, legislation on Cd use was put to limit the exponential rise in its environmental levels. This study aimed to investigate Cd's functional and ultrastructural changes on rats' reproductive system and the possible protective role of Zingiber officinale (Ginger) against Cd-induced toxicity. Methods: Thirty adult male albino rats were randomly assigned into three equal groups (n=10); control, Cd-exposed/untreated, and Cd-exposed/Gin-treated. Rat testes were weighed, and testicular tissue sections were examined under the electron microscope. Semen analysis, morphological examination of spermatozoa, and serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone were measured. Besides, testicular tissue homogenates were analyzed for malondialdehyde (MDA), nitric oxide (NO), and reduced glutathione (GSH) levels. Results: Cd-induced significant reduction in the mean testicular weight and GSH levels and plasma testosterone, LH and FSH levels with a concomitant increase in testicular MDA and NO levels. There was also deterioration in semen analysis parameters and spermatozoa morphology together with testicular structural damage in the form of architecture distortion and necrosis of seminiferous tubules and testicular interstitial cells. Daily administration of ginger for four weeks had a protective effect against CD-induced toxicity in the form of tissue-architecture preservation, improved plasma levels of testosterone, LH and FSH and testicular levels of MDA, NO, and GSH. Conclusions: Ginger has a protective effect on Cd-induced deterioration of testicular tissue's structural and functional integrity by improving testicular tissue anti-oxidant capacity and steroid production, which ameliorates sex hormone levels in the blood.